Utilizing Financial Technology (Fintech) to Drive Increased Economic Growth - Kumalasari, Dewi; Farida, Alimatul (LPPM Institut Bisnis dan Informatika Kesatuan, 2024)
This research aims to examine the concept of Financial Technology (Fintech) in more depth and explain the use of fintech to encourage increased economic growth through BMT and MSMEs. The use of fintech for BMT and MSMEs includes providing loans, all processes are done online, payment technology is carried out en masse, you can check payments, technology makes payments easier. This research is library research with a thematic interpretation method. The use of fintech encourages increased economic growth through BMT and MSMEs by studying a number of studies regarding the concept of fintech ontologically and epistemologically with the aim of analyzing various perspectives related to fintech and its benefits. The results of this research state that the use of fintech in encouraging increased economic growth through BMT and MSMEs has great potential. This research shows that the use of fintech can encourage increased economic growth through BMT and MSMEs. The resulting benefits and positive impacts include easier access to financing, operational efficiency and reduced administrative costs, increased market access and marketing, better education and financial literacy, as well as contributions to local and national economic growth.